Ethical Integrity and Transformational Leadership in Implementing STEM-Based Merdeka Curriculum in Rural Elementary Schools - Daniel Sudibyo Tjandra (Indonesian Journal of Educational Research and Review, 2025)
The limited resources that can integrate transformational leadership and ethical integrity to support the implementation of the STEM-based Independent Curriculum are the main focus that must be resolved. This study aims to analyze how ethical academic integrity is embedded within the transformational leadership practices of an elementary school principal implementing the STEM-based Merdeka Curriculum in a rural setting. The research focuses on five leadership dimensions: idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, and an added ethical integrity dimension. A qualitative case study approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis, and then coded thematically using ATLAS.ti. The findings integrated ethical principles into decision-making, organizational communication, and resource distribution. These practices fostered an inclusive environment that encouraged innovation, cross-generational collaboration, and institutional trust, despite the school’s structural limitations. The principal empowered teachers to experiment with STEM instructional strategies, provided personalized support, and maintained transparency in curriculum-related decisions. Collectively, these actions demonstrate that a transformational leadership model grounded in ethical integrity significantly contributed to the success of curriculum reform in a marginalized school context. The study concludes that ethical leadership is not merely complementary to transformational leadership but integral to sustaining educational change in under-resourced environments. It is recommended that school leadership development programs emphasize ethical decision-making and value-driven leadership, particularly for principals serving in disadvantaged educational settings.